The Effect of Using Augmented Reality to Lower Anxiety in Phobia Patients: Pengaruh Penggunaan Augmented Reality untuk Menurunkan Kecemasan pada Penderita Fobia - Anggara, Onny Fransinata; Rahmasari, Diana; Savira, Siti Ina; Dewi, Damajanti Kusuma; Budiani, Meita Santi; Satiningsih, Satiningsih (Procedia of Social Sciences and Humanities, 2024)
Augmented Reality (AR) has emerged as a promising technology in the mental health field with the potential to change the approach to the management of anxiety disorders, including phobias. This study aims to explore the effectiveness of AR therapy in reducing anxiety levels in phobia sufferers, with a focus on patients' experiences and responses to this technology. The research method used was an experimental study with a Randomized Controlled Trial (RCT) design, involving two groups of participants: an experimental group that received AR therapy and a control group that did not receive the intervention or received conventional therapy. Measurements were carried out using a valid and reliable anxiety scale before and after the intervention to assess changes in anxiety symptoms. The results showed that AR therapy significantly reduced anxiety levels in participants in the experimental group compared to the control group. Participants who underwent AR therapy reported increased tolerance for previously fear-inducing situations, as well as improvements in their daily quality of life. In conclusion, the use of AR in phobia therapy offers an innovative and effective approach to reducing anxiety symptoms in phobia sufferers. By creating a controlled virtual environment, AR facilitates safe and scalable exposure to therapy for patients, overcoming some of the barriers that exist in conventional therapy. The clinical implications and potential further application of this technology in clinical practice need to be further investigated to maximize its benefits in the management of anxiety disorders.